Encapsulation of 2, 2′-(decane-1, 10-diyl)-diisoquinoline into cucurbit[6]uril and α, α′, δ, δ′-tetramethyl-cucurbit[6]uril: formation of pseudorotaxanes and polypseudorotaxanes†. Issue 5 (4th May 2017) - Fan, Zhi-Fang; Lin, Rui-Lian; Sun, Wen-Qi; Tao, Zhu; Liu, Jing-Xin
Abstract: Host–guest complexation of cucurbit[6]uril and α, α′, δ, δ′-tetramethyl-cucurbit[6]uril with 2, 2′-(decane-1, 10-diyl)-diisoquinolinium has been investigated by 1 H NMR, UV and fluorescence spectroscopy in aqueous solution and by X-ray crystallography in solid state. Experimental data suggest that in the aqueous solution, both host molecules form [2]pseudorotaxanes with the host located over the decyl chain of the guest. In the solid state, neighbouring [2]pseudorotaxanes are linked by π⋯π and C–H⋯π interactions, eventually generating polypseudorotaxanes. Abstract :